La Colonia Digital Archive: New Haven's Italian American Community, 1890–1930 - Larkin, Erin (2026)
La Colonia Digital Archive: New Haven's Italian American Community, 1890–1930 is an open-access digital humanities project documenting the professional and civic life of New Haven's Italian American community between 1890 and 1930. The archive is based on Antonio Cannelli's La Colonia Italiana di New Haven (1921), a 373-page Italian-language volume combining a community Who's Who with a survival guide for new immigrants. Cannelli documented 248 individuals and more than 90 businesses, including physicians, attorneys, pharmacists, musicians, grocers, and bankers. Cannelli published his volume in 1921, the same year that Nicola Sacco and Bartolomeo Vanzetti went on trial for murder in Massachusetts; they were convicted on July 14, 1921, and sentenced to death in a case that became an international cause célèbre and a defining watershed of anti-immigrant sentiment directed specifically at Italians. The trial unfolded against a broader landscape of systematic exclusion: the Emergency Quota Act of 1921 had passed just months earlier, sharply restricting Southern and Eastern European immigration, and Italians faced sustained targeting, marginalization, and persistent characterization as unskilled, unassimilable, and threatening. Cannelli's documentation was deliberate advocacy in precisely this climate: a counter-narrative assembled to demonstrate the professional achievement, civic engagement, and cultural diversity and richness of a community that dominant American discourse refused to acknowledge. La Colonia Digital Archive makes that narrative searchable and accessible to researchers, descendants, and the general public, plotting archival documents and photographs onto contemporary maps of New Haven and the surrounding area. The archive is currently in active pre-launch development. Public release is planned for 2026, with ArcGIS StoryMap components to be added through 2026–2027.
Keywords: Cultural heritage; Digital Archives; Diversity (politics); Documentation; Haven; Narrative; dept.wll

Turning to returnees - Schmitt, Elena (Linguistic Approaches to Bilingualism, 2025)
Keywords: dept.wll

Humanistic Education: A Collection of Reflective Essays - Narvaez, George (Independently published, 2025)
Humanistic Education: A Collection of Reflective Essays by George Narvaez is a compelling anthology that bridges classical philosophy, modern educational theory, and personal reflection. Drawing on the author’s graduate studies at Harrison Middleton University, these twenty essays offer a deep dive into the evolution of human thought on education, knowledge, and the art of learning.This book is ideal for readers interested in the humanities, education, philosophy, or self-directed learning. It engages with timeless questions:What does it mean to “know” something?How is knowledge constructed and communicated?How can education empower individuals and communities?Inside this collection, you will explore:✔️ The foundational philosophies of Plato, Aristotle, Augustine, and Aquinas✔️ Modern insights from William James, John Dewey, and Benjamin Franklin✔️ The evolution of rhetoric and epistemology across history✔️ The relationship between language, culture, and cognition✔️ The author's transformative journey through educationEach essay combines academic rigor with accessible language, offering readers a path to understand how classical theories of liberal education connect with contemporary learning practices. From the “education of the hemispheres” in William James’s psychology to the experiential learning of Franklin and Dewey, the author shows that learning is not just about absorbing information—it’s about transforming the way we live, communicate, and understand ourselves and others.Key themes include:Rhetoric as a tool for empowermentEpistemology as a process of inquiryCivic responsibility through educationPersonal growth through humanistic reflectionWhether you're an educator, student, scholar, or lifelong learner, Humanistic Education is a thought-provoking guide to the intellectual traditions that continue to shape our educational ideals.Start your journey through the minds of history’s greatest thinkers—and reflect on your own learning path.

Bilingual autobiographical memory: unveiling the significance of memories encoded in multiple languages - Sorokina, Anastasia (Multilingua, 2025)
Keywords: Autobiographical memory; Cognitive psychology; Cognitive science; Computer science; Linguistics; Philosophy; Psychology; Recall; bilingual autobiographical memory; dept.wll; memory phenomenology; mixed memories; peer-reviewed

“It’s where she belongs, isn’t it?” Lupe Vélez and Dolores del Río in Hollywood - Hernández-Rodríguez, R. (Nomadic New Women: Exile and Border-Crossing between Spain and the Americas, Early to Mid-Twentieth Century, 2024)
Mexican artistic influence at the beginning of the twentieth century was prevalent in America, most notably muralism, but also talent associated with the movies. This influenced the way Mexico was perceived in the United States, and by extension the way Lupe Vélez and Dolores del Río, the most successful Mexican actresses in early Hollywood, were appreciated. Both actresses had come to Hollywood to fulfill their dream of a career in the movies. At first, they were successful playing a variety of roles in silent movies, but once sound arrived, their accents made obvious their foreignness at a time when American culture was beginning to spread around the world and to establish its preeminence. They were aware of the challenges they faced and knew there was a price to pay if they wanted to continue in a business where the public decided, at a time when Americans distrusted foreigners. So, if that price was to overplay her earthy Mexicaness, in the case of Vélez, or emphasize her aristocratic image, in the case of del Río, they were ready to pay it. Mexico became the other par excellence in the early twentieth century, and these heavily accented actresses were evidence of that.
Keywords: Dolores del Río; Ethnic representation; Hollywood; Identity; Lupe Vélez; Mexican influence; Silent films; Stereotypes; Talkies; dept.wll

Challenges and achievements of an online intercultural exchange in time of crisis - Fornara, F; Gleason, Jesse (How We Take Action: Social Justice in PK-16 Language Classrooms, 2023)
How We Take Action brings together practical examples of social justice in language education from a wide range of contexts. Many language teachers have a desire to teach in justice-oriented ways, but perhaps also feel frustration at how hard it is to teach in ways that we did not experience ourselves as learners and have not observed as colleagues. As a profession, we need more ideas, more examples, and wider networks of allies in this work. This book includes the work of 59 different authors including teachers and researchers at every level from Pre-K to postsecondary, representing different backgrounds, languages, and approaches to classroom practice. Organized into three sections, some of the chapters in this collection report on classroom research while others focus on key practices and experiences. Section I is entitled Inclusive and Empowering Classrooms. In this section authors take a critical approach to classroom practices by breaking with the status quo or creating spaces where students experience safety, access, and empowerment in language learning experiences. Section II, Integration of Critical Topics, addresses a variety of ways teachers can incorporate justice-oriented pedagogies in day-to-day instructional experiences. Social justice does not happen haphazardly; it requires careful, critical examination of instructional practices and intentional planning as instructors hope to enact change. Section III, Activism and Community Engagement, explores how teachers can empower students to become agents for positive change through the study of activism and constructive community engagement programs at local and global levels.
Keywords: dept.wll

Embracing bilingualism: L1 retention amidst L2 acquisition - Sorokina, A.; Mugno, R. (Language Learning Journal, 2024)
In L1 attrition research, it's recognized that a previously acquired language can transform under the influence of a newly acquired one. However, the precise L1-L2 relationship is intricate and warrants further study. Some research suggest that L2 mastery might reduce L1 proficiency, while others show that both languages can be maintained. Age of onset and L1 use are the factors that have been discussed in the debate surrounding L1 attrition. The study aims to contribute to the ongoing discussion by examining L1 and L2 proficiency of Russian-English bilingual speakers (N = 35). The participants with comparable L2 proficiency but various degrees of L1 attrition who arrived at different ages and differed in their frequency of L1 use were recruited for the study. This diverse group provided an ideal quality sample for investigating the role of age of onset and L1 use, as well as the interplay between L1 and L2. By comparing L1 and L2 lexical diversity, syntactic complexity, and fluency, the study revealed that higher L2 proficiency was not associated with lower levels of L1 proficiency, suggesting that L1 retention is possible amidst L2 acquisition. L1 use played a more significant role in the L1 maintenance of these bilingual individuals. © 2024 Association for Language Learning.
Keywords: L1 attrition; L1 maintenance; L1 use; age of onset; bilingualism; dept.mat; dept.wll; peer-reviewed

A Century of Italian War Narratives: Voices from the Sidelines - Gussago, Luigi; Palma, Pina (Brill, 2023)
Keywords: Contemporary History; Criticism & Theory; Cultural History; History; Literary Relations; Literature and Cultural Studies; Memory Studies; dept.wll

A case study on the role of project-based learning in improving university students’ speaking skills: From theory to practice - Trihn, Nguyen Thi Tu; Schmitt, Elena (Konińskie Studia Językowe, 2020)
The aims of this paper are twofold: (1) to study the application of project-based learning ten-step process framework suggested by Alan and Stoller (2005) to boost English speaking ability of undergraduate students at the University of Da Nang, and (2) to investigate the levels of undergraduate students’ satisfaction. The subjects were 24 final year undergraduate engineering students at the university of Da Nang during the first semester of the 2019/2020 academic year. The instruments used in this experiment included lesson plans, a project evaluation form, a student’s self-assessment form, a satisfaction questionnaire and interviews
Keywords: English speaking skills; dept.wll; peer-reviewed; project-based learning; self-assessment

The knowledge framework for building teacher awareness of language in content instruction - Schmitt, Elena; Gleason, Jesse (Social Practices in Higher Education; A Knowledge Framework Approach to Linguistic Research and Teaching; Slater, 2023)
Keywords: dept.wll

Bilingualism - Schmitt, Elena G. (Encyclopedia of Slavic Languages and Linguistics Online, 2023)
Keywords: dept.wll

Ecocritical Reflections on Fiction Written by Nobel Laureate Mario Vargas Llosa - Flores, W. (Humanidades, 2023)
This article examines anthropocentric and ecocentric tendencies in two major works written by Mario Vargas Llosa, The Storyteller and The Dream of the Celt, to identify the value of those novels in ecocritical terms. I provide this analysis in the context of recent academic dialogue which notes an apparent contradictory relationship between the presentation of abuses of Amazonian people and their environment, and the portrayal of Westernized protagonists as their saviors in fiction written by Vargas Llosa. This essay provides a solution to this paradox and other apparent contradictions in his narratives and posits that even though the anthropocentric literary discourse concerning the environment has declined throughout the latter part of the twentieth century, in part, due to the rise of the environmental movement, this type of discourse has changed in Vargas Llosa’s literature, rejecting early twentieth century misconceptions of the natural world but holding onto technocentric neoliberal beliefs. © 2023, University of Montevideo. All rights reserved.
Keywords: Mario Vargas Llosa; Peruvian literature; The Dream of the Celt; The Storyteller; dept.wll; ecocriticism; environment; peer-reviewed

Coping with a language loss: A case of linguistic and cultural re-encoding of memories in language attriters - Sorokina, Anastasia (International Journal of Bilingualism, 2023)
Aims and objectives:This study investigates the effects of language loss on bilingual autobiographical memory. More specifically, the study focuses on whether severe language loss would lead to any linguistic changes and/or interfere with how memories are recalled and shared.Methodology:Autobiographical memories were elicited with the help of a cued-recall technique and memory questionnaire from two groups of immigrants?attriters (who experienced significant language loss) and bilinguals (who retained their first language proficiency).Data and analysis:The data set consisted of pre-immigration memories that were originally encoded in the first language, Russian. The frequency of recall (i.e., sharing memories with others as well as reminiscing) and linguistic components (i.e., words) of memories elicited from the attriters and bilinguals were analyzed quantitatively and qualitatively.Findings and conclusion:Overall, attriters were able to recall memories that were originally encoded in the forgotten language. They also reported reminiscing about their pre-immigration memories and sharing their memories with others. However, attriters revealed that the pre-immigration memories came to them with words in the second language, English, which was not the case with bilinguals. Attriters also reframed memories for several Russian culture-specific items and events. This finding is indicative of memory re-encoding?a phenomenon when memories are updated, stored, and subsequently retrieved with added information. While this finding points to the bilingual mind?s ability to adapt to language loss, it may also suggest linguistic and cultural assimilation under the influence of the new language and culture.Originality:This is the first investigation of autobiographical memory in bilinguals with severe language loss that highlights the malleability and adaptability of the bilingual mind as well as the importance of language maintenance.
Keywords: dept.wll; peer-reviewed

Food Cultures of Mexico: Recipes, Customs, and Issues - Hernández Rodríguez, Rafael (Global kitchen (Greenwood Press (Westport, Conn.)), 2021)
"This exciting volume brings to life the food culture of Mexico, detailing the development of the cuisine and providing practical information about ingredients and cooking techniques so that readers can replicate some of Mexico's most important traditional dishes"--
Keywords: Cooking / Regional & Ethnic / Central American & South American; Cooking / Regional & Ethnic / Mexican; Food habits; History / Latin America / Mexico; Mexico; Cooking, Mexican; Mexico; Social life and customs; dept.wll

Developing self-directed learning strategies through creative writing: Three case studies of snowball writing practice in a college Chinese language classroom - Tu, I. Ju (Thinking Skills and Creativity, 2021)
This study investigates three learners’ self-directed learning (SDL) strategies in a college beginner level Chinese language classroom. Using a focus group and interviews to explore how the students recognize their own learning strengths and weaknesses, what strategies they develop during the SDL process, their awareness of learning contexts while adopting SDL, and how they exercise their agencies for SDL. Findings suggest that technology fluency, the disconnection between learning goals and SDL strategies, and learners’ unawareness of their learning strengths affects individuals’ agency regarding SDL strategies. These findings suggest the need for further discussion of language teachers’ role in instructing SDL strategies, the role of technology, and the use of written corrective feedback. © 2021
Keywords: dept.wll; peer-reviewed

Empirical insights into college students’ academic reading comprehension in the united states - Kalbfleisch, Elizabeth; Schmitt, Elena; Zipoli, Richard P. (Journal of College Reading and Learning, 2021)
This article reports on a collaborative research project involving faculty in writing studies, communication disorders, and applied linguistics that sought to empirically describe the reading skills of students (N = 910) in freshman composition classes at one college and two universities in the northeast United States. The research team developed and administered a questionnaire that evaluated students’ reading abilities according to six categories: inferential ability, background knowledge, general comprehension, vocabulary, figurative language/jargon, and morphosyntactic structures (grammar/syntax). Our statistically significant results showed that students scored best in the categories of background knowledge and general comprehension, which are well researched in a college population. However, students struggled in categories such as figurative language/jargon and morpho-syntactic structures, which are not well researched in a college population. Further, comprehension seemed generally discrete (understanding specific points of an essay) rather than holistic (indicated by an ability synthesize those points into a general statement about the author’s thesis). These findings suggest that further empirical research in this area will help describe the reading skills of college students and consequently will inform the development of pedagogical approaches that more effectively address students’ current needs. © 2021 College Reading and Learning Association.
Keywords: dept.cmd; dept.eng; dept.wll; peer-reviewed

Redemptive children and historical memory: Luis mateo díez’s la gloria de los niños (2007) - Weng, Miaowei (Bulletin of Spanish Studies, 2020)
This article explores contemporary Spanish writer Luis Mateo Díez’s 2007 novel, La gloria de los niños, focusing on the construction of a redemptive child who mends the broken world and keeps alive historical memory. The author looks beyond one single nation state in his reconstruction of children and childhood under the Franco regime. Hidden behind his approach to the reconstruction of the ‘glorious children’ under Franco emerges, on the one hand, his dissolution of any authoritative version of Franco-era children and, on the other, his broader vision and desire to examine Spain and Spanish historical memory in a global context. © 2020 Bulletin of Spanish Studies.
Keywords: Childhood under Franco; Historical Memory; La gloria de los niños; Ladri di biciclette (1948); Luis Mateo Díez; Post Civil War period; Redemptive Child; Vittorio de Sica; Walter Benjamin; dept.wll; peer-reviewed

The knowledge framework for building teacher awareness of language in content instruction - Gleason, Jesse; Schmitt, Elena (Social practices in higher education - A knowledge framework approach to linguistic research and teaching, 2021)
Keywords: dept.wll; faculty_collection